Hydrocarbons in bottom sediments of the marginal filter of the Volga River. - Nemirovskaya, Inna A; Brekhovskikh, V F (PANGAEA, 2006)
Materials from different spheres of the Earth are ultimately delivered to bottom sediments, which serve as a natural recorder of the functioning of other spheres and originate as a result of the accumulation of their substances. Sedimentary material and species of river-transported elements are subjected to dramatic reworking in marginal filters, where river and sea waters are mixed. These processes are most important for the Caspian Sea, where runoffs of rivers (especially the Volga River) and the intense development and transportation of hydrocarbon fuel by tankers and pipelines (related to the coastal petroleum industry in the Sumgait and Baku ports, Apsheron Peninsula) are potential sources of hydrocarbon pollution. Previously obtained data showed that the total content of hydrocarbon fraction (i.e., the sum of aliphatic hydrocarbons (AHC) and polycyclic aromatic hydrocarbons (PAH)) in bottom sediments varied within 29-1820 µg/g. The content of petroleum hydrocarbons in the northeastern Caspian region varied from 0.052 to 34.09 µg/g with the maximum content in the Tengiz field. The content of six polyarenes in the Volga delta sediments was no more than 40 ng/g. To determine the recent HC pollution of bottom sediments and trends in the functioning of the Volga marginal filter, in summer of 2003 and 2004 we analyzed bottom sediments (58 samples) in the river waterway; Kirovsk channel; Bakhtemir and Ikryanoe branches; tributaries of the Kizan, Chagan, and other rivers; and the Caspian seashore.
(Table) Content of organic compounds in the bottom sediments of the Volga River estuary
Keywords: Aliphatic hydrocarbons; Aliphatic hydrocarbons per unit mass total organic carbon; Archive of Ocean Data; ARCOD; Carbon, organic, total; Caspian Sea; Date; DEPTH, sediment/rock; Infrared spectrophotometry; Liquid chromatography; Perylene; Phenanthrene/anthracene ratio; Polycyclic aromatic hydrocarbons; Polycyclic aromatic hydrocarbons, per unit mass organic carbon; Ratio; Sample ID; Sediment type; Volga03-11; Volga03-13; Volga03-14; Volga03-15; Volga03-16; Volga03-18; Volga03-19; Volga03-20; Volga04-10; Volga04-15; Volga04-19; Volga04-20; Volga04-21; Volga04-22; Volga04-23; Volga04-24; Volga04-25; Volga04-26; Volga04-27; Volga04-28; Volga04-29; Volga04-3; Volga04-30; Volga04-4; Volga04-7; Water content, wet mass